MENCIPTA LAGU DARI PUISI: LOKAKARYA KREATIF UNTUK MUSISI NONPROFESIONAL: CREATING SONG FROM POETRY: A CREATIVE WORKSHOP FOR NONPROFESSIONAL MUSICIANS - Adi Wijaya; Jonathan Irene Sartika Dewi Max; Royke Bobby Koapaha (Program Studi Sastra Indonesia Universitas Mulawarman, 2026)
Abstract: This community service activity aims to bridge the gap between the high appreciation of poetry and the technical ability of music composition among non-professional musicians and students. The method used was a music concert and workshop over three days in Cibenda Village, West Java. The target group included high school students without a formal music education background. The implementation stages included the presentation of basic material on songwriting, understanding the relationship between text and music, mentoring group work practices, and presentations of work. The results of the activity showed that the practical approach successfully synergized literary appreciation with technical musical skills. Participants were able to understand the structure of popular songs, chord progressions, and scales, and translate the emotional character of poetry into musical compositions. The tangible output of this workshop was the creation of complete musical works by each group, the building of self-confidence and motivation for music creation among participants, and the formation of the embryo of a sustainable music learning community as a medium for creative expression. Keywords: creative workshop; community service; music composition; musicalized poetry; nonprofessional musicians Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk menjembatani kesenjangan antara tingginya apresiasi puisi dan keterbatasan keterampilan teknis komposisi musik pada musisi nonprofesional dan pelajar. Metode yang digunakan adalah pelaksanaan perkemahan musik dan lokakarya selama tiga hari di Desa Cibenda, Jawa Barat. Sasaran kegiatan meliputi pelajar tingkat atas tanpa latar belakang pendidikan musik formal. Tahapan pelaksanaan mencakup pemaparan materi dasar penciptaan lagu, pemahaman relasi teks dan musik, pendampingan praktik pengkaryaan kelompok, serta presentasi karya. Hasil kegiatan menunjukkan bahwa pendekatan praktis berhasil menyinergikan apresiasi sastra dengan keterampilan teknis musik. Peserta mampu memahami struktur lagu populer, progresi akor, dan tangga nada, serta menerjemahkan karakter emosional puisi ke dalam komposisi nada. Luaran nyata dari lokakarya ini adalah terciptanya karya musik utuh dari setiap kelompok, terbangunnya kepercayaan diri dan motivasi penciptaan musik para peserta, dan terbentuknya embrio komunitas belajar musik yang berkelanjutan sebagai medium ekspresi kreatif. Kata kunci: komposisi musik; lokakarya kreatif; musikalisasi puisi; musisi nonprofesional; pengabdian masyarakat